(untitled) (Construction Economics and Building, 2015)
General management research has increasingly recognised the significance of routines in organisational performance. Among organisational tasks, megaprojects depend more on routines selected and created within the project than standard, small-scale projects do, owing largely to their size, duration, and uniqueness. Within this context, the present paper investigates how project routines were established and developed during the early design phase of an inter-organisational megaproject. A case study of a large public infrastructure project was conducted, in which data were collected during observations, semi-structured interviews, and project document studies over the course of three years. Results of analysis revealed that the client exerted the greatest impact on choice of routines and that the temporary nature of tasks limited efforts to fine-tune routines. Changes in routines were primarily reactive to new knowledge concerning project needs. The findings suggest that meta-routines to consciously review routines should be used to a greater extent and designed to capture supplier experiences as well.